Antioxidant and tyrosinase inhibitory activity of face serum containing cocoa pod husk phytosome (Theobroma cacao L.) - Sani Ega Priani, Saskara Aprilia, Ratih Aryani, Leni Purwanti (Journal of Applied Pharmaceutical Science, 2019)
High polyphenol content of cocoa pod extract causing it potential to be developed as antioxidant and tyrosinase inhibitory agent in cosmetic preparations. Phytosome system known could enhance skin penetration of phytoconstituent like polyphenol-rich extract. The objectives of this research were to formulate phytosome containing cocoa pod extract, develop phytosome complex into face serum preparation, and determine antioxidant and tyrosinase inhibitory activities of the extract and the formulated serum. The cocoa pod extract was developed into phytosome system by thin-layer method using soy-phosphatidylcholine. The phytosome then develop into face serum formulation using Viscolam MAC 10 as a gelling agent. The antioxidant activity was conducted by 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay and tyrosinase inhibitory activity was conducted by colorimetric enzymatic assay. The cocoa pod extract has very strong antioxidant activity with inhibitory concentration (IC50) of 17.21 ppm. The extract also has tyrosinase inhibitory activity with IC50 of 199.98 ppm. The phytosome complex containing cocoa pod extract and phosphatidylcholine (1:1) has good entrapment efficiency (90.5%) with an average particle size of 672 nm. The formulated face serum has good physical characteristic and also has antioxidant and tyrosinase inhibitory activities that equal with the marketed product (Hadalabo ultimate whitening milk, Rohto, Indonesia).
Keywords: Cocoa pod husk, phytosome, serum, inhibitor tyrosinase, antioxidant.